2017
DOI: 10.1016/j.thromres.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism with aspirin compared to anticoagulants after hip and knee arthroplasty

Abstract: Background Recent guidelines include aspirin as an option to prevent venous thromboembolism (VTE) in selected patients undergoing hip or knee replacement surgery. However, the efficacy of aspirin after arthroplasty has not been well-defined, particularly in more contemporary patient populations. We compared rates of post-operative VTE between patients who received aspirin-only versus anticoagulants after hip or knee arthroplasty, using data from a large US-based administrative database. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…Compared with previous findings, the frequency of using aspirin-only for postoperativethromboprophylaxis in patients undergoing knee or hip arthroplasty was higher in our study. 6,17 Our previous retrospective cohort study which similarly investigated thromboembolic risk in a large nationally representative sample of patients receiving aspirin compared with anticoagulation after knee or hip replacement surgery between 2009 and 2012 in the USA found that aspirin-only was administered in 7.5-8% of cases, 6 while this proportion increased to more than 27% in our current study that covered a timeframe after publication of the updated American College of Chest Physicians (ACCP) guidelines. Similarly, a recent retrospective chart review of 329 patients undergoing knee arthroplasty at 2 tertiary care centers found that the proportion of patients receiving monotherapy with aspirin for postoperative thromboprophylaxis increased from 4.6 to 44.4% in the periods before and after the publication of ACCP guidelines in 2012 18 ; in these updated guidelines, the use of aspirin as a sole thromboprophylactic agent after knee or hip arthroplasty was newly endorsed and hence, consensus was reached with the recommendations made by the American Academy of Orthopedic Surgeons (AAOS).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Compared with previous findings, the frequency of using aspirin-only for postoperativethromboprophylaxis in patients undergoing knee or hip arthroplasty was higher in our study. 6,17 Our previous retrospective cohort study which similarly investigated thromboembolic risk in a large nationally representative sample of patients receiving aspirin compared with anticoagulation after knee or hip replacement surgery between 2009 and 2012 in the USA found that aspirin-only was administered in 7.5-8% of cases, 6 while this proportion increased to more than 27% in our current study that covered a timeframe after publication of the updated American College of Chest Physicians (ACCP) guidelines. Similarly, a recent retrospective chart review of 329 patients undergoing knee arthroplasty at 2 tertiary care centers found that the proportion of patients receiving monotherapy with aspirin for postoperative thromboprophylaxis increased from 4.6 to 44.4% in the periods before and after the publication of ACCP guidelines in 2012 18 ; in these updated guidelines, the use of aspirin as a sole thromboprophylactic agent after knee or hip arthroplasty was newly endorsed and hence, consensus was reached with the recommendations made by the American Academy of Orthopedic Surgeons (AAOS).…”
Section: Discussionmentioning
confidence: 56%
“…10 Venous thromboembolism diagnoses included lower extremity deep vein thrombosis and pulmonary embolism events and were based on ICD-9 codes (online Supplemental Table 1). 6,9,11 Follow-up for thromboembolic events started at the day of surgery. Events that occurred after discharge and led to readmission within 30 days were based on primary diagnosis codes for venous thromboembolism, and we also considered outpatient encounters for venous thromboembolism within 90 days after discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the literature is controversial on recommending ASA as a single agent for thromboprophylaxis, recent studies 44 demonstrate that it can be used after a short five-day cycle of a directacting oral anticoagulant (rivaroxaban) in hip and knee arthroplasties. 45,46 Studies on ASA as a thromboprophylaxis agent in ankle and foot surgeries are still scarce, as noted in a recent consensus on the subject. 17 Unfractionated heparin and LMWH inhibit several coagulation proteases (►Figure 2).…”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 99%
“…For clinicians who care for joint arthroplasty patients postoperatively, this study adds to the growing literature supporting the use of aspirin as an acceptable option in preventing post-operative VTE. [3][4][5] As acknowledged by the authors, an ongoing randomized, head-to-head comparison of aspirin vs. other agents will likely better answer this question (PEPPER trial). Moreover, this work further establishes the need to develop a risk assessment tool and best practice recommendation that incorporates individual thrombosis risk (e.g., malignancy, h/o prior VTE) balanced by bleed risk to prospectively select appropriate candidates for aspirin prophylaxis in patients following arthroplasty.…”
mentioning
confidence: 99%